Penentuan Sektor Ekonomi Unggulan dengan Analisis Overlay di Kota Surabaya - Elva Afria Suwarno; Sishadiyati Sishadiyati (UNIVED Press, 2022)
People's well-being can be improved through the use of regional leading sectors. The amount of regional output based on the performance of individual or overall economic sectors to determine the size of regional economic growth is known as Gross Regional Domestic Product (GRDP). Based on GRDP data from 2015 to 2020, a study was conducted in Surabaya with the goal of identifying the leading sectors, understanding the performance of economic sectors, understanding the grouping of sectors, and understand the role of leading sectors for the return of regional economic conditions. The research method is based on a quantitative approach using the LQ analysis method, shift share, and Klassen typology, followed by overlay analysis to reach conclusions. According to the calculations, 11 economic sectors were identified as superior in the LQ analysis, 1 economic sector received positive results in both components in the shift share analysis, and 4 economic sectors were classified as Quadrant 1 in the Klassen typological classification. Referring to these results, the financial services and insurance sectors are the only sectors that meet positive results in all three analysis tools. So, according to overlay analysis, the financial services and insurance sector in Surabaya is a leading economic sector that can be used to improve the economy due to the covid-19 pandemic